The Power of Gono-Gini in The Formation of Political Dynasty: Family Party Power in 2020 Simultaneous Regional Elections - Syauket, Amalia; Lestiyani, Tri Endah Karya (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
There are 29 of the 57 women running for the 2020 simultaneous regional elections who are the wives of previous regional heads. Thus, in the fourth episode of the simultaneous regional elections, the same problems as the previous simultaneous regional elections, namely the pragmatism of political parties in recruitment, ultimately fostered political dynasties at the local level. The political dynasty model which makes the wife the regional head has developed in several regions with the same pattern, namely that all of them are wives where the husband is the regional head who has served for two consecutive terms. The practice of administering government is likened to the joint power of husband and wife, passed down from generation to generation as if it were a family institution or private institution. This phenomenological type qualitative research aims to find out what is the main purpose of nominating his wife in the regional head election after her husband's period of service is over? and in what route does the wife become a candidate for regional head so that a political dynasty is formed? The results of this academic research show that in the process of forming a political dynasty by design, in the third stage, the wife is promoted to the regional head candidacy, with the main aim of maintaining power and wealth. Novelty: the strength of masculinity in government means that wives are exploited to maintain power and wealth in the formation of political dynasties.